GEOLOGY OF THE EASTERN SØR RONDANE MOUNTAINS, EAST ANTARCTICA - ASAMI, Masao; MAKIMOTO, Hiroshi; GREW, Edward S. (National Institute of Polar Research, 1989)
P(論文) The eastern Sør Rondane Mountains (71°40′-72°20′S; 26°30′-28°E), which was surveyed by the summer field party of JARE-29 in early 1988,is underlain by a high-grade migmatized gneissic complex consisting largely of metasedimentary and metavolcanic rocks, and subordinate metaigneous rocks and unmetamorphosed diorite and granite-pegmatite intrusions. Upper amphibolite to hornblende granulite-facies metamorphism was followed by an amphibolite-facies event, which is closely related with the migmatization. This sequence is indicated by the widespread occurrence of primary orthopyroxene-and sillimanite-bearing mineral assemblages, and secondary cummingtonite and green hornblende replacing pyroxenes and secondary biotite replacing garnet. Metadikes of biotitic schist, typically hornblende-biotite-plagioclase-quartz, which cut the gneisses, are considered to have been intruded between the two metamorphic events. A late, greenschist-facies event is suggested by the alteration of high-temperature mafic minerals to calcite, chlorite, epidote, muscovite and margarite. Earlier, recumbent isoclinal folds, and later upright more open folds could correspond to the early high-grade metamorphism and the amphibolite-facies event, respectively. Fault zones with displacements of several meters to 10m or more are abundant and could also be related to the amphibolite facies event. departmental bulletin paper